Entre o graffiti e o pós-graffiti : a construção das identidades estéticas e profissionais de grafiteiros no âmbito da arte urbana em Porto Alegre - Mendes, Fernanda Brasil (Universidade do Vale do Rio dos Sinos, 2018)
To understand the insertion of young graffiti artists in the labor market and the process of construction of their aesthetic and professional identities, were investigated the unfolding and new contours that they are creating for their insertions in the labor market and for the dissemination of their artwork. Graffiti gains new configurations and new meanings in the work context, called here post-graffiti. Initially, is presented the historical context of the graffiti, as well as its issues in relation to politics and aesthetics and the discussions and interpretations around graffiti. Next, are analyzed the issues involving the world of work and how it influences the culture of graffiti and the profile of graffiti artists. Then, post-graffiti is contextualized, being a hybrid product, originated from new social formations and from the dissemination of new identifications, thus being a professional path for graffiti artists. What strategies are used for the insertion and the maintenance of graffiti artists in the post-graffiti labor market? How does the process of constructing the aesthetics and identities of the graffiti artists surveyed take place? These issues are the subject of discussion in order to facilitate the understanding of the process of transition from the aesthetic and professional identities of young graffiti artists in relation to the labor market in the framework of the creative economy.
Keywords: Graffiti; Pós-graffiti; Economia criativa; Identidades; Graffiti; Post-graffiti; Creative economy; Identities; ACCNPQ::Ciências Humanas::Sociologia